ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI POLA KONSUMSI MAHASISWA FAKULTAS EKONOMI UNIZAR MATARAM - Lilis Suryani; Baiq Rizka Milania Ulfah (Nusantara Hasana Berdikari, 2022)
This study aims to determine the factors that influence the pattern of non-food consumption in students of the economics faculty of UNIZAR Mataram. This research was conducted on 73 students of the economics faculty using multiple linear regression analysis method. The results showed that partially (t test) income had a significant effect on students' non-food consumption patterns, lifestyle had a significant effect on students' non-food consumption patterns. Based on the simultaneous test (F test) shows that there is an effect of income and lifestyle on non-food consumption patterns of students of the economics faculty of UNIZAR Mataram.